2012
DOI: 10.1111/php.12001
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Solar Ultraviolet‐B Radiation in the Citrus Red Mite, An Upper Surface User of Host Plant Leaves

Abstract: Plant-dwelling mites are potentially exposed to solar ultraviolet-B (UVB) radiation that causes deleterious and often lethal effects, leading most mites to inhabit the lower (underside) leaf surfaces. However, in species of spider mite belonging to the Genus Panonychus, a substantial portion of individuals occur on upper leaf surfaces. We investigated whether the upper leaf surfaces of citrus trees are favorable for P. citri, and to what extent they are tolerant to UVB radiation. If eggs are not adequately pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
(65 reference statements)
1
26
0
1
Order By: Relevance
“…For P. maculiventris, the first condition could be met if predation pressure is higher on the undersides of leaves, as has been observed in other plant-dwelling arthropod systems [12,15]. The upper surface of leaves would then represent ''enemy free space'' [30,31], and applying the pigment when eggs are laid there would minimize the cost of the resulting tradeoff in terms of higher UV radiation exposure. The second condition could be met if there is a significant physiological cost of pigment production, as demonstrated in many other systems [24,32,33].…”
Section: The Egg Pigment Is Not Melaninmentioning
confidence: 96%
“…For P. maculiventris, the first condition could be met if predation pressure is higher on the undersides of leaves, as has been observed in other plant-dwelling arthropod systems [12,15]. The upper surface of leaves would then represent ''enemy free space'' [30,31], and applying the pigment when eggs are laid there would minimize the cost of the resulting tradeoff in terms of higher UV radiation exposure. The second condition could be met if there is a significant physiological cost of pigment production, as demonstrated in many other systems [24,32,33].…”
Section: The Egg Pigment Is Not Melaninmentioning
confidence: 96%
“…Carrillo et al (2014) also reported low population densities of A. largoensis on coconut seedlings in glasshouse experiments. Solar radiation, especially UVB, may be lethal to predatory mites and favor the development of some phytophagous mites (Fukaya et al, 2013). In the present study, the leaf abaxial surface of the seedlings, onto which prey and predators had been released, was greatly exposed to sunlight, differently from most leaves of fully-grown plants.…”
Section: Amblyseius Largoensis In Controlling Red Palm Mite Under Semmentioning
confidence: 68%
“…Among the morphological responses of plants to UV-B stress, LIA and root/shoot ration (RSR) are regarded as typical responses (Fukaya et al 2013). The reduced LIA and RSR in UV-stressed C. roseus seedlings were obviously observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ultraviolet-B (UV-B) radiation produces a wide diversity of morphological and physiological damages to plant growth and metabolism, photosynthetic performance, and chloroplast membrane components (Ali et al 2010;Lidon & Ramalho 2011;Pandey et al 2011;Fukaya et al 2013;Singh et al 2013). UV-B-absorbing compounds such as flavonoids are considered as a critical barrier for protecting plants from UV-B stress (NunezOlivera et al 2009;Fabon et al 2012).…”
Section: Introductionmentioning
confidence: 99%